Biological Crust of Soil in Wadi AL-Ram Basin Using Remote Sensing Technology (Study in Environmental Geography (Journal of Libya for geographical studies, 2025)
Following the existence of biological crust in the soil and changing its distribution spatially and temporally is important in the management of ecosystems in desert areas, It provides very important information on the study of desertification and climate change in dry environments, The aim of the research is to reveal the distribution and change of the distribution of the biological crust of the soil in Wadi Al-Ram basin using remote sensing technology, The results of the research found that the area of the area that is characterized by the density of the biological cortex changed by positive in different periods, This is confirmed by an increase in the area of the biological crust of the soil by 33.3 km2 between 2000 and 1990, and the area increased by 42.1 km2 between 2018 and 2000.
Keywords: Soil; Biological Soil crust; AL-Ram Wadi; Remote Sensing